Who saw her die? - Moyes, Patricia (Felony & Mayhem Press, 2018)
"When Lady Balaclava is murdered at a weekend house party, her daughters emerge as the most likely suspects, and Inspector Henry Tibbett heads off to the Continent to check on their alibis"--
Keywords: Tibbett, Henry (Fictitious character) -- Fiction; Tibbett, Emmy (Fictitious character) -- Fiction; Police -- Great Britain -- Fiction; Murder -- Investigation -- Fiction; Mystery fiction